Estructura de datos XTCE en sistemas CubeSat - Figueredo, Wilmer; Aparicio Pico, Lilia Edith (Revista Científica, 2021)
This article shows the construction of an information model for the exchange of data and information within the context of the development of CubeSat type satellite systems; articulating the development, procedure, description, design, architecture and results that largely refer to the adoption of such guidelines within a scenario of technological interoperability and specifying the functionality in the transmission patterns of telemetry information in academic satellites. The guidelines of the Consultative Committee on Spatial Data Systems (CCSDS) are taken into account in collaboration with the European Space Agency (ESA) and the European Cooperation for Spatial Standardization (ECSS), who have consolidated multiple recommendations to standardize the transfer of information from space systems through various procedures and mechanisms. Additionally, the Extensive Markup Language (XML) was considered, next to the Telemetry and Command Exchange (XTCE) format, in conjunction with the Package Utilization Standard (PUS), the description of Mission Operation Services (MO) and the Message Abstraction (MAL) layer, taking into account that they suggest the modularity and specificity necessary for the development and construction of information systems in satellite technologies.